Planning the costs of EU projects at state universities - Szczepaniak, Waldemar (Planowanie kosztów w projektach unijnych na uczelniach publicznych, 2021)
The main purpose of the study was to assess importance of the cost planning process in the procedure of applying and the practice of spending EU funds by state universities in Poland. In pursuit of this goal, the literature and EU guidelines were analysed, and a survey of EU project managers at state technical universities was additionally carried out. During the study, reference was made to issues such as determining resources needed to implement an EU project, ensuring financing for their own contribution and ineligible costs. The literature studies, the analysis of programming documents of the current financial perspective and the results of the survey, indicate the key role of cost planning in the effective acquisition and settlement of projects co-financed from EU funds. The expected reduction of EU funds for Poland under subsequent financial perspectives will result in further difficulties in obtaining funding. In order to increase the absorption capacity of EU funds, state universities should pay special attention to the cost planning process, providing project initiators with specialized support in budget construction and justification of planned costs
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2021; vol. 65, nr 2, s. 150-158